A Study on the Volatility Effects of Listing of Equity Options and Equity Futures in National Stock Exchange of India - Mattack, Tulika; Saha, Ashit (Indian Journal of Finance, 2016)
Ever since their introduction in various stock exchanges of the world, financial derivatives have been an interesting area of study, a major concern being their impact on the volatility of the underlying securities. Considering the phenomenal growth of the derivatives market in India together with the fact that studies around the world lack in consensus regarding the impact of futures and options on market volatility, an in-depth study of the Indian market was felt necessary. This study aimed to find out whether introduction of options and futures contracts had an effect on the volatility of the underlying equities. The results from the ARMA-GARCH models applied in the study proved that volatility of most of the underlying stocks decreased with the listing of equity options and futures.